Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear - Zawierucha, Krzysztof; GĄsiorek, Piotr; Buda, Jakub; Uetake, Jun; Janko, Karel; Fontaneto, Diego (Zootaxa, 2018)
Glaciers and ice sheets are a peculiar biome with characteristic abiotic and biotic components. Mountain glaciers are predicted to decrease their volume and even to melt away within a few decades. Despite the threat of a disappearing biome, the diversity and the role of microscopic animals as consumers at higher trophic levels in the glacial biome still remain largely unknown. In this study, we report data on tardigrades and rotifers found in glacial mosses on Mount Stanley, Uganda, and describe a new tardigrade species. Adropion afroglacialis sp. nov. differs from the most similar species by having granulation on the cuticle, absence of cuticular bars under the claws, and a different macroplacoid length sequence. We also provide a morphological diagnosis for another unknown tardigrade species of the genus Hypsibius. The rotifers belonged to the families Philodinidae and Habrotrochidae. In addition, we discuss the diversity of microinvertebrates and potential role of tardigrades and rotifers on mountain glaciers as top consumers. As for any organism living apparently exclusively in glacial habitats on tropical glaciers, their extinction in the near future is inevitable, possibly before we can even discover their existence.
Keywords: Tardigrada; Bryophyta; Animals; Tardigrada, Adropion afroglacialis sp. nov., biodiversity loss, endangered habitats, extreme ecosystems, extremophiles, Hypsibius, tropical glaciers, Uganda; zvířata; vířníci; Ice Cover; Uganda; Rotifera; ledový příkrov